EFEKTIVITAS ASAP CAIR DARI LIMBAH TEMPURUNG KELAPA SEBAGAI BIOPESTISIDA BENIH DI GUDANG PENYIMPANAN - Arinto Nugroho; Imas Aisyah (Jurnal Penelitian Hasil Hutan, 2013)
Liquid smoke was formed as condensation product during the process of wood pirolysis at temperature around 400°C). Phenolic compounds, aldebrydes, ketones, alcohols, organic acids and ester, could functioned as antimcidants and anti-microbes (anti-bacteria and anti-fungi). This research aimed to study the effectivity of liquid smoke from coconий shell waste as alternative agent to control the attack by seed pests (i.e. fungi) on the plant seed stored in the wareboun, of the Plant Serding Departement, Vocational Education Development Center for Agriculture (VEDCA). The Initial step of the research was the production of liquid smoke from coconut shell, the obtained liquid smoke was then sprayed everly auto corn seeds and soybean seeds at four different concentration: 0%, (control), 0.5%, 1%, and 2% (v/v). Each of with were made in 3 replications, re-drying process was then done to let the west reache its optimum moisture content. Concentration 3 replications were made. The seedt were then packed in abeat flour sack and rach kept for 72 days. Samples were then taken at day-0, day 36 and day-72 for observation on germination test and wed bealth testing (insensity of fungi attack). The treatment of liquid make with varying concentration, ie 0.5%, 1%, and 2% trught about significane different in germination of both corn and soybean seeds after wurthouse storage for 72 days, and 0.5% concentration showed the best Feralt.